Preparation and characterization of PLA/algae nanocomposite for packaging industry - Adli, Sarah Amalina; Ali, Fathilah; Azmi, Azlin Suhaida (Penerbit Akademia Baru, 2018)
Nowadays, the usage of plastic packaging raises environmental concern as they accumulated on landfill. Hence, biodegradable polymer is introduced to substitute conventional plastic in the packaging industry. Currently, biopolymers are studied extensively and some of them shows potential to substitute non-degradable plastic, but one biopolymer (polylactic acid (PLA)) in particular stands out as it possesses the same properties as conventional plastic like polystyrene and polyester. Though, PLA’s slow degradation rate and brittleness limit its application. Therefore, this study aims to overcome the limitations of PLA and widen its application by modifying them. In this study, algae is used as a filler to lower the cost and increase degradation rate while epoxidized palm oil (EPO) is used as plasticizer to increase the flexibility of PLA. Plasticized PLA (PLAEPO) is mixed using 5 wt% of algae filler content. The composite is prepared by two methods; solvent casting and melt mixing. For solvent casting, PLA and algae are dissolved in chloroform and casted by evaporation whereas for melt mixing, all materials are melt blended using an internal mixer. Characterization for the flexibility, thermal, mechanical and morphological properties of PLAEPO/algae composite is conducted by using flexibility test, differential scanning calorimetry (DSC), tensile testing and scanning electron microscopy respectively. After further discussion and consideration, it is decided that PLAEPO/ALG-5 is best prepared by solvent casting method.